Identification and selection of reference genes for analysis of gene expression by quantitative real-time PCR in the euhalophyte Suaeda altissima (L.) Pall. - Dmitrii E. Khramov; Olga I. Nedelyaeva; Alena O. Konoshenkova; Vadim S. Volkov; Yurii V. Balnokin (Communicative & Integrative Biology)
Сoding sequences of seven housekeeping genes: actin SaACT7, ubiquitin-conjugating protein SaUBC10, glyceraldehyde-3-phosphate dehydrogenase SaGAPDH, protein of the large subunit of ribosomes SaL2, α-tubulin SaTUA, translation elongation factor SaeEF1α, and protein phosphatase SaPP2A were identified as candidate reference genes for expression analysis of target genes in the extremely salt tolerant plant Suaeda altissima (L.) Pall. The expression profiles of the genes differed. SaACT7 and SaeEF1α demonstrated the highest expression levels, while the lowest expression levels were found for SaPP2A and SaTUA. SaPP2A and SaeEF1α genes were the most stably expressed at different steady-state salinity levels and different nitrate concentrations in nutrient solutions (NSs). SaL2, SaPP2A, and SaeEF1α genes showed the greatest stability of expression when nitrate was added to nutrient solution of plants grown under conditions of nitrate deficiency. Less constant expression was demonstrated in this experiment by SaACT7 and SaTUA. SaL2, SaACT7, SaeEF1α, and SaUBC10 genes showed the smallest expression changes under salt shock. To validate the use of the most stably expressed genes for normalization of gene expression, we checked them as reference genes to study the expression of the nitrate transporter gene SaNPF6.3 in S. altissima roots under conditions of different salinity and different nitrate supply.